USING SIRI AS A MEDIUM TO IMPROVE SPEAKING SKILLS - Tyas, Anjar Hayuning (Jurnal Kajian Pembelajaran dan Keilmuan, 2026)
This study aims to determine the effectiveness of using Siri as a tool to improve the English speaking skills of eighth grade students at SMP Muhammadiyah 22 Pamulang. Technology has become an important part of education, helping students learn English in an engaging and interactive way. Siri, a virtual assistant based on artificial intelligence (AI), provides instant feedback that helps learners improve their confidence, fluency, and pronunciation through consistent, engaging communication. The study used a quasi-experimental design to divide students into two groups. The experimental group learned to speak with Siri, while the control group used traditional learning techniques. Pronunciation, fluency, grammar, and vocabulary were measured before and after data were collected. The results of statistical analysis showed that the experimental group had higher post-test scores than the control group. These findings show that, despite minor limitations such as accent recognition and device dependency, Siri can effectively help students improve their speaking skills by providing instant feedback and encouraging autonomous learning beyond the classroom.